Soil-biodegradable mulch is an alternative to non-biodegradable plastic mulches in a strawberry-lettuce double-cropping system - Wang, Xuechun; Shrestha, Srijana; Tymon, Lydia; Zhang, Huan; Miles, Carol; DeVetter, Lisa (Frontiers in Sustainable Food Systems, 2022)
Double cropping strawberry (Fragaraia ×ananassa Duch.) and lettuce (Lactuca sativa L.) could be a sustainable alternative practice for diversified specialty crop growers. Plastic mulch is beneficial for strawberry and lettuce production with soil-biodegradable mulch (BDM) providing opportunities to reduce plastic waste generation and costs of mulch disposal. The objective of this study was to compare nonbiodegradable plastic mulches and BDM to bare ground cultivation in a strawberry-lettuce double cropping system in a Mediterranean climate. A split-plot randomized complete block design experiment with mulch treatment [nonbiodegradable polyethylene (PE) film, “weedmat” (woven, PE-based), BDM and bare ground control] as the main factor and double cropping rotation scheme (rotation 1 or 2) as the split plot factor was conducted between 2020-2021. Strawberry yield was overall greatest when mulched with BDM, PE, and weedmat compared to the bare ground control. Strawberry total soluble solids (TSS), pH and total titratable acidity (TA) all differed due to harvest date but only pH differed due to mulch treatment. For lettuce canopy cover, rotation 2 had greater canopy cover (86%) compared with rotation 1 (66%) 30 days after transplanting. Average head weight (0.4 kg) and head length and diameter (both 20 cm) did not differ due to mulch or rotation. Average soil temperatures under PE and BDM were approximately 1.5 ℃ higher than under weedmat, and 2.5 ℃ higher than the bare ground control. Soil under weedmat had the highest moisture content whereas the PE, BDM, and bare ground treatments had similar levels. PE, BDM, and weedmat provided equivalent weed suppression whereas the bare ground control had the most weeds. BDM deterioration estimated as percent soil exposure (PSE) was greatest (59% PSE) by the end of the experiment whereas PE had 18% PSE and weedmat had no deterioration. Results show that despite high levels of deterioration, BDM performs similarly to PE in terms of soil temperature and moisture modification, weed suppression, and promotion of crop growth and yield in a double-cropped system. Double cropping strawberry and lettuce is a promising alternative for growers to diversify their crop type and with potential economic benefits by increasing mulch lifespan.